PENERAPAN STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) MENGGUNAKAN ALAT PERAGA UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA - Anugraini, Asri Putri; Muflihah (Universitas Insan Budi Utomo, 2021)
The development of science and technology allows all parties to obtain abundant information quickly and easily from various sources and places in the world. Students have the ability to think critically, systematically, logically, creatively, and the willingness to work together effectively so that it is possible to be skilled in rational thinking. The results of initial observations can be seen that most students have difficulty understanding mathematical material, so it is clear when the teacher asks about the material that has been delivered, students still look confused with the material presented by the teacher. The delivery of mathematics subject matter still uses conventional learning and the use/use of learning media in the form of teaching aids is still limited. From the problems found, the researcher decided to use the STAD type cooperative method by using mathematics property as a research action. This classroom action research was focused on class VIII MTs students.Miftahul Ulum Gondanglegi on the material of cube and cuboid which was carried out by researchers in two cycles. Cycle I showed that 20% of students had completed learning, the rest had not reached the success criteria, namely 80%. This was because in terms of several activities which include giving quizzes, group discussions, presentations, doing test questions, they still do not meet the expected success criteria due to lack of confidence, lack of communication between students and teachers during discussions and presentations, students were still afraid to ask questions and were afraid to answer. So it seems less cooperative. Cycle II gives individual points of improvement based on the criteria specified in the STAD type cooperative method. Students show the ability to ask questions, answer questions, in group discussions. Students were active in assembling cooperative teaching aids in discussion activities. Learning outcomes have increased reaching 90.47%.